Molecular Mechanisms of the Whole DNA Repair System: A Comparison of Bacterial and Eukaryotic Systems - Rihito Morita; Shuhei Nakane; Atsuhiro Shimada; Masao Inoue; Hitoshi Iino; Taisuke Wakamatsu; Kenji Fukui; Noriko Nakagawa; Ryoji Masui; Seiki Kuramitsu (Journal of Nucleic Acids)
DNA is subjected to many endogenous and exogenous damages. All organisms have developed a complex network of DNA repair mechanisms. A variety of different DNA repair pathways have been reported: direct reversal, base excision repair, nucleotide excision repair, mismatch repair, and recombination repair pathways. Recent studies of the fundamental mechanisms for DNA repair processes have revealed a complexity beyond that initially expected, with inter- and intrapathway complementation as well as functional interactions between proteins involved in repair pathways. In this paper we give a broad overview of the whole DNA repair system and focus on the molecular basis of the repair machineries, particularly in Thermus thermophilus HB8.